Hutan Adat dan Kelas Menengah: Titik Balik Reforma Agraria di Indonesia? - Iskandar Zulkarnain (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2017)
The turning point of the agrarian reform of the customary forest arena after the Constitutional Court's Decision 35/PUU-X/2012 can not be based on state domination (government) through the agenda of territorialization of the forest and not on AMAN as representation of indigenous struggle from the paradox of interest. Bringing the alternative of a critical new middle class, as well as running a deliberation democracy through representational politics that combine extra parliamentary and intra-parliamentary struggles simultaneously in organizational form, capable of realizing sustainable agrarian reform. The new middle class struggle is a synthesis of the dialectic of forest recognition and the existence of indigenous peoples undergoing involution.